A longitudinal analysis of the changing roles of gender in advertising: a content analysis of Super Bowl commercials. Issue 5 (2nd September 2016) - Hatzithomas, Leonidas; Boutsouki, Christina; Ziamou, Paschalina
Abstract : Although the prevalence of gender stereotypes in advertising is well established, relatively little research has examined gender stereotypes in the context of Super Bowl that is arguably the most important event in US television advertising. This study systematically examines gender representations across various product categories in Super Bowl commercials over a 20-year period (1990–2009). Our findings detect and discuss shifts in the cultural notions of gender constructed in advertising messages targeting the largest and the most demographically diverse audience in US television. The paper concludes with a discussion of the theoretical and managerial implications of our findings.